Tackling the E-Commerce Frontier: Navigating Public Service Challenges Amidst the Pandemic - Jannah, Miftakhul; Muchsin, Slamet; Hayat (GoAcademica Research & Publishing, 2024)
The COVID-19 pandemic has brought significant challenges to public services, including limitations on face-to-face interactions. As a result, e-commerce has emerged as a potential solution to provide public services online. This study aims to identify the challenges and variables in implementing e-commerce for public services during the pandemic in Indonesia. The study uses a literature review method, which includes collecting data through documentation and online data tracking. The data collected were analyzed to identify the challenges and variables in implementing e-commerce for public services during the pandemic. The study found that the challenges in implementing e-commerce for public services during the pandemic in Indonesia include technical issues, lack of infrastructure, limited citizen support, and legal regulations. The variables that affect the implementation of e-commerce for public services include quality of service, efficiency, and adequate infrastructure. The implementation of e-commerce for public services during the pandemic in Indonesia faces various challenges and requires improvements in quality of service, efficiency, and infrastructure. The study suggests that the government and e-commerce marketplaces should work together to address these challenges and improve the implementation of e-commerce for public services.